The Impact of Traditional and Modern Practices on Maternal Health During the Postpartum Period - Andi Muhammad Multazam; Isah Fitriani; Annisa Andriyani (Journal of Public Health Indonesian, 2026)
This mixed-method study demonstrates that postpartum care practices significantly influence maternal health outcomes, with modern practices and integrated traditional–modern approaches yielding better results than reliance on traditional practices alone. Quantitative findings indicate that mothers who adopted evidence-based postpartum care experienced improved physical recovery and overall health status, while qualitative insights reveal that traditional practices continue to play an important psychosocial and cultural role. The integration of both approaches emerged as the most beneficial model, suggesting that maternal health outcomes are optimized when biomedical care is complemented by culturally meaningful practices that provide emotional support and social reassurance. The findings carry important implications for maternal health policy and practice. Health professionals should avoid framing traditional postpartum practices as inherently harmful and instead adopt culturally sensitive strategies that encourage safe integration with modern care. Training programs for midwives and postpartum care providers should emphasize respectful communication and cultural competence to enhance maternal trust and service utilization. However, this study has limitations. The findings are context-specific and may not be fully generalizable to regions with different cultural or healthcare systems. Additionally, the cross-sectional nature of the quantitative phase limits causal inference, and self-reported health measures may be subject to recall bias. Future research should employ longitudinal designs and broader geographic coverage to further examine the long-term health effects of integrated postpartum care models.